2015
DOI: 10.1098/rspa.2014.0905
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of air resonance power efficiency in the violin and its ancestors

Abstract: The fact that acoustic radiation from a violin at air-cavity resonance is monopolar and can be determined by pure volume change is used to help explain related aspects of violin design evolution. By determining the acoustic conductance of arbitrarily shaped sound holes, it is found that air flow at the perimeter rather than the broader sound-hole area dominates acoustic conductance, and coupling between compressible air within the violin and its elastic structure lowers the Helmholtz resonance frequency from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 46 publications
3
54
0
Order By: Relevance
“…Nia et al have recently reported that the f-holes gradually lengthened going from Amati to Stradivari violin models. Based on computer simulation, they predicted the air resonance mode of Stradivari violins to carry higher frequency and greater power ( 6 ). Our data demonstrate that Strad violins also produce higher F1 to F4 formants than other old Italian violins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nia et al have recently reported that the f-holes gradually lengthened going from Amati to Stradivari violin models. Based on computer simulation, they predicted the air resonance mode of Stradivari violins to carry higher frequency and greater power ( 6 ). Our data demonstrate that Strad violins also produce higher F1 to F4 formants than other old Italian violins.…”
Section: Discussionmentioning
confidence: 99%
“…Among the old masters, Stradivari’s instruments are the most preferred by modern soloists, and his models are also the most copied by modern makers. Construction differences between Amati and Stradivari violins have been carefully studied, including plate geometry ( 2 , 4 , 5 ), f-hole design ( 6 ), varnishing methods ( 7 ), and so on. However, the tonal distinctions between Stradivari and Amati violins remain poorly understood.…”
mentioning
confidence: 99%
“…But only up to a point: psychophysical thresholds exist and there are clearly natural laws governing much of the way humans hear and experience sound. 20,21,22 One of the most promising approaches to studying the impact of sound on humans has been combining audio content feature analysis (based on a sound's physical properties), with measures of human experience (such as Self-Assessment Manikin surveys on arousal and valence after listening). 23,24 Using properties of sound as features and experience measures as labels for those features, several groups have attempted to build machine learning algorithms that can predict emotional responses based on the sound properties alone, commonly according to a valence-arousal circumplex model.…”
Section: A Effects Of Sound On Human Experiencementioning
confidence: 99%
“…A consensus among experts is that these instruments deliver superior sounds to violins made since the Baroque era, and there have been several hypotheses-both scientifically supported and unsupported ones-attempting to elucidate the cause of such a superior sound quality. Claims range from a mysterious ingredient to the wood, or a secret varnish recipe (Echard et al, 2010;Mancini, Tromba, & Zanini, 2006;Nagyvary, DiVerdi, Owen, & Tolley, 2006;Nia et al, 2015), to the instruments' unique shape and even good old-fashioned genius of the ancient master violinmakers. However, the most convincing evidence relates to the climate at that time, where the "little Ice Age" (Mauder Minimum, 1645-1715 caused European spruces (Picea abies) that form the instruments' top plate to grow regularly, giving the instrument a fuller and more consistent sound (Burckle & Grissino-Mayer, 2003;Stoel & Borman, 2008).Making modern-day bow instruments superior may mean trying to recreate the effect of cold climate on wood, which we managed to achieve with the help of wood-decomposing fungi.…”
Section: The Mother Of All VI Olin Smentioning
confidence: 99%